2018
DOI: 10.1136/jech-2017-209074
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy body mass index and breastfeeding initiation, early cessation and longevity: evidence from the first wave of the UK Millennium Cohort Study

Abstract: The causal mechanisms underlying relationships between pre-pregnancy overweight, obesity, and breastfeeding behaviours require further research. However, this study suggests pre-pregnancy BMI as one predictive measure for targeting support to women less likely to establish breastfeeding in the early days, and to continue beyond 4 months. The nature of support should carefully be considered and developed, with mind to both intended and potential unintended consequences of intervention given the need for additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In addition, for those studies in which there was a report for number and/or percent of initiation/intention of BF by levels of BMI, we calculated the crude OR/RR [ 2 , 11 , 22 , 27 , 28 , 29 , 30 , 31 , 32 ]. In order to calculate OR for the association between levels of BMI and BF, and if the authors used the non-initiation/intention group as reference, we calculated OR by the proportion of non-initiation/intention of BF to initiation/intention of BF (by using the reciprocal characteristic of OR) [ 1 , 7 , 27 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Also, in a study by Hilson et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, for those studies in which there was a report for number and/or percent of initiation/intention of BF by levels of BMI, we calculated the crude OR/RR [ 2 , 11 , 22 , 27 , 28 , 29 , 30 , 31 , 32 ]. In order to calculate OR for the association between levels of BMI and BF, and if the authors used the non-initiation/intention group as reference, we calculated OR by the proportion of non-initiation/intention of BF to initiation/intention of BF (by using the reciprocal characteristic of OR) [ 1 , 7 , 27 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Also, in a study by Hilson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Ascertaining these exposures prior to pregnancy is also a strength as compared with many studies that obtained pre-pregnancy weight from selfreports during pregnancy. 33 The study has some limitations. First, we cannot identify whether the associations of pre-pregnancy IFG and BMI with LGA and PTB were modified by pregnancy complications (pre-eclampsia and gestational diabetes) because most of the participants (99.1%) did not test Epidemiology/Health services research for gestational diabetes and pre-eclampsia.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…Open access rural Australian populations, these rates have been consistently lower than that reported in urban populations with exclusive breast feeding decreasing in all almost immediately following hospital discharge resulting in less than 20% of babies being exclusively breast fed by 6 months. 4 High maternal body mass index (BMI) is negatively associated with breast feeding initiation, [5][6][7][8] but it remains unclear if the association is confounded by other risk factors such as mother's age, low socioeconomic status (SES), comorbidities or antenatal, intrapartum or postpartum conditions or neonate's overall health. 9 10 Changes in breast feeding initiation rates across three national surveys in Australia concluded that although these rates increased from 86% in 1995 to 88% in 2004-2005, they were consistently lower in women belonging to lower socioeconomic groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%